Essays on Environmental Economics - Abdelkader, Mamdouh (Université d'Ottawa / University of Ottawa, 2025)
This dissertation investigates how diverse policy levers can drive the transition to a low-carbon economy. The first chapter uses dynamic system GMM panel estimation on U.S. electricity sector data (2000-2015), grounded in a theoretical framework inspired by the Directed Technical Change literature, to compare carbon pricing, clean energy tax incentives, and R&D subsidies. It finds that price-based instruments, such as carbon pricing and clean energy tax credits, induce a more immediate and pronounced shift toward renewable generation than R&D subsidies, underscoring the effectiveness of price signals in accelerating the energy transition. The second chapter develops a dynamic general equilibrium model to evaluate a broader suite of climate policies. These include carbon pricing, R&D subsidies, dirty investment taxes, and clean investment tax credits. Policies targeting high-emission sectors, notably carbon pricing, effectively cut emissions due to these sectors' significant market share, but may negatively impact economic prosperity. To balance emissions reduction and economic vitality, the essay proposes a clean "double dividend" strategy, using revenues from dirty-sector taxes to fund clean-sector incentives. This provides a balanced pathway toward reducing emissions while sustaining economic performance. Finally, the third chapter turns to monetary policy, using a structural vector autoregression to quantify how interest rate shocks affect CO₂ emissions across U.S. sectors. It finds that contractionary monetary policy produces a persistent yet transitory negative effect on total CO₂ emissions. These monetary policy shocks primarily affect industrial emissions while minimally impacting the residential and commercial sectors. Given central banks' limited capacity to directly influence environmental outcomes, monetary policy should thus be considered complementary to fiscal policy and environmental regulation in addressing climate change.
Keywords: Directed Technical Change; Environmental Policy; Carbon Pricing; R&D Subsidies; Tax Incentives; System GMM; Dynamic General Equilibrium Model; CO2 Emissions; Monetary Policy; Structural VAR